Pengaruh Atribut Produk Terhadap Keputusan Pembelian Sabun Pencuci Piring Mamalime di Bumiayu - Lufti Fitriani; Cici Widowati (Universitas Peradaban, 2016)
This study is a survey research which conducted on the consumer of Mamalime product in Bumiayu. This study investigates the influence of product attributes, which consisted of packaging, price perception, brand, product quality, and label, to the purchasing decision of Mamalime product consumer in Bumiayu. The population of this study are all of Mamalime product consumer in Bumiayu, and the total sample is 100 respondents which chosen by using non-probability sampling method (convenience sampling). Data that used in this study are consisted of primary data that are taken from questionnaire, and secondary data that are obtained from literatures. The result of this study shows that (1) packaging doesn’t significantly influence to the purchasing decision of Mamalime product consumer in Bumiayu, (2) price perception significantly influences to the purchasing of Mamalime product consumer in Bumiayu, (3) brand significantly influences to the purchasing decision of Mamalime product consumer in Bumiayu, (4) product quality significantly influences to the purchasing decision of Mamalime product consumer in Bumiayu, and (5) label doesn’t significantly influence to the purchasing decision of Mamalime product consumer in Bumiayu.